GUIDANCE BASED ON SURAH AL-FATIHAH TO INCREASE THE FAITH OF CONVERTS IN DZAL HAJRA KUBU RAYA DISTRICT WEST KALIMANTAN - MUHAMMAD HIQQAL; MUHAMMAD EDI KURNANTO (Universitas Islam Negeri Mataram, 2023)
This research is motivated by the low faith of converts because they have not properly practiced worship according to Islamic law. Converts to worship only limited to fulfilling their obligations as a Muslim are not internalized and practiced in everyday life. This study aims to obtain an overview of the faith of converts before and after being given guidance based on surah Al-Fatihah and to see the effectiveness of guidance based on surah Al-Fatihah in increasing converts' faith. The level of faith that often fluctuates makes converts must always try to maintain their faith so that it always increases every day. Increased faith is very influential on the consistency of worship and practice in the daily life of converts. This study uses a mixed research method (mixed method) by making two groups consisting of an experimental group and a control group. The resulting data were analyzed using the t test of the two most independent samples (independent t test). The resulting data shows that the average value of the control group is smaller than the average value of the experimental group, which means that there is an increase in the effectiveness of surah Al-Fatihah-based guidance in increasing the faith of converts. The results of the research conducted obtained a significance of 0.00 which is smaller than 0.05, so that H0 was rejected and Ha was accepted. From these results it is known that there is an increase and the effectiveness of surah Al-Fatihah-based guidance in increasing the faith of converts.